Monitoring Alpha Oscillations and Pupil Dilation across a Performance-Intensity Function - McMahon, Catherine M.; Boisvert, Isabelle; de Lissa, Peter; Granger, Louise; Ibrahim, Ronny; Lo, Chi Yhun; Miles, Kelly; Graham, Petra L. (Frontiers in Psychology, 2016)
Listening to degraded speech can be challenging and requires a continuous investment of cognitive resources, which is more challenging for those with hearing loss. However, while alpha power (8-12 Hz) and pupil dilation have been suggested as objective correlates of listening effort, it is not clear whether they assess the same cognitive processes involved, or other sensory and/or neurophysiological mechanisms that are associated with the task. Therefore, the aim of this study is to compare alpha power and pupil dilation during a sentence recognition task in 15 randomized levels of noise (-7dB to +7dB SNR) using highly intelligible (16 channel vocoded) and moderately intelligible (6 channel vocoded) speech. Twenty young normal hearing adults participated in the study; however, due to extraneous noise, data from 16 (10 females, 6 males; aged 19-28 years) was used in the EEG analysis and 10 in the pupil analysis. Behavioral testing of perceived effort and speech performance was assessed at 3 fixed SNRs per participant and was comparable to sentence recognition performance assessed in the physiological test session for both 16- and 6-channel vocoded sentences. Results showed a significant interaction between channel vocoding for both the alpha power and the pupil size changes. While both measures significantly decreased with more positive SNRs for the 16-channel vocoding, this was not observed with the 6-channel vocoding. The results of this study suggest that these measures may encode different processes involved in speech perception, which show similar trends for highly intelligible speech, but diverge for more spectrally degraded speech. The results to date suggest that these objective correlates of listening effort, and the cognitive processes involved in listening effort, are not yet sufficiently well understood to be used within a clinical setting.